Smart-AD: Mobile Application for Event Advertising - Khairilanwar, Nur Athirah (IRC, 2020)
In UTP, extra-curricular activities are considered as partial requirements for students. However, even with the increasing demands and growth of events, not many students tend to participate or join the events. One of the reasons is because there is no proper event advertising platform for students in UTP. Therefore, the objective of this project is to create a mobile application as an integrated platform for advertising events, make it on or off campus events or collaborations with other universities or organizations to increase and motivate students’ involvements and engagements in events.